The Decrease in Farnesoid X Receptor, Pregnane X Receptor and Constitutive Androstane Receptor in the Liver after Intestinal Ischemia-Reperfusion - Jiro Ogura; Yusuke Terada; Takashi Tsujimoto; Takahiro Koizumi; Kaori Kuwayama; Hajime Maruyama; Asuka Fujikawa; Atsushi Takaya; Masaki Kobayashi; Shirou Itagaki; Natsuko Takahashi; Takeshi Hirano; et al. (Frontiers Media S.A., 2012)
Purpose. Intestinal ischemia-reperfusion (I/R) damages remote organs, including the liver, and promotes multi-organ failure (MOF). However, the molecular mechanisms underlying acute liver injury after intestinal I/R have not been completely elucidated. Farnesoid X receptor (FXR), pregnane X receptor (PXR) and constitutive androstane receptor (CAR) regulate metabolizing enzymes and transporters, and coordinately prevent hepatotoxicity reflecting an inability of appropriate excretion of endogenous toxic compounds. In this study, we assessed FXR, PXR and CAR expression levels and their localization levels in nuclei in the liver after intestinal I/R. We also investigated the effect of IL-6 on FXR, PXR and CAR expression levels and their localization levels in nuclei in in vitro experiments. Methods. We used intestinal I/R model rats. Moreover, HepG2 cells were used in in vitro study. Real-time PCR and Western blotting were used to assess mRNA and protein expression levels. Nuclear receptor localization in nuclei was analyzed by Western blotting using nuclear extracts. Results. FXR and PXR expression levels began to be decreased at 3 h, and FXR, PXR and CAR expression levels were decreased at 6 h after intestinal I/R. The localization levels of FXR, PXR and CAR in nuclei began to be decreased at 3 h, and all of them were decreased at 6 h after intestinal I/R. In HepG2 cells, FXR, PXR and CAR expression levels were decreased by 0.5-1 ng/mL, 0.5-100 ng/mL and 100 ng/mL IL-6 treatment for 24 h, respectively. FXR, PXR and CAR localization levels in nuclei were suppressed by 0.5-10 ng/mL, 10-100 ng/mL and 10-100 ng/mL IL-6 treatment for 24 h, respectively. Conclusions. FXR, PXR and CAR expression levels are decreased in the liver after intestinal I/R. IL-6 is one of main causes the decreases in expressions of these receptors. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.